"Make (America) Chile Great Again" (Observatorio Económico, 2017)
The title of this article is inspired by the slogan of the campaign that carried Donald Trump to the presidency of the United States. A phrase that, beneath the surface, sought to explain the loss of jobs and the flight of companies to other countries through globalization. A discourse that struck a deep chord with a majority of the American electorate. Continue reading...
Keywords: Chilean economy; Economic growth; Productivity